Dynamic functional connectivity impairments in idiopathic rapid eye movement sleep behavior disorder. (October 2020) - Li, Guanglu; Zhou, Liche; Chen, Zhichun; Luo, Ningdi; Niu, Mengyue; Li, Yuanyuan; Kang, Wenyan; Liu, Jun
Abstract: Introduction: Previous functional magnetic resonance imaging (fMRI) studies typically analyzed static functional connectivity (sFC) to reveal the pathophysiology of iRBD and overlooked the dynamic nature of brain activity. Thus, we aimed to explore whether iRBD showed abnormalities of brain network dynamics using the dynamic functional connectivity (dFC) approach. Methods: Resting-state fMRI data from 33 iRBD patients and 38 matched healthy controls were analyzed using an independent component analysis, sliding window correlation and k -means clustering. Relationships between clinical symptoms and abnormal dFC were evaluated using Spearman's correlation analysis. Results: Four distinct connectivity states were identified to characterize and compare dFC patterns. We demonstrated that iRBD had fewer occurrences and a shorter dwell time in the infrequent and strongly connected State 1, but with more occurrences and a longer dwell time in the frequent and sparsely connected State 2. In addition, iRBD patients showed significantly decreased FC in certain dFC states compared to healthy controls. More importantly, the impairments in the temporal properties of State 2 were found to be associated RBDSQ scores in the patient group. Conclusions: This study detected dFC impairments in iRBD patients and provided new insights into the pathophysiology of iRBD, which might contribute to the development of disease-modifying drugs in future clinical trials. Highlights: iRBD showed impaired temporal properties of dFC compared to healthy controls. iRBD patients showed significantly decreased FC in certain dFC states. Altered temporal properties of dFC were associated with disease severity in iRBD. These findings give us new insights into the pathophysiology of iRBD.